Differences in Sexual Health, Sexual Behaviors, and Evaluation of the Last Sexual Event Between Older and Younger Bisexual Men. Issue 1 (2nd January 2016) - Schnarrs, Phillip W.; Rosenberger, Joshua G.; Novak, David S.
Abstract: Research has shown that compared to younger individuals, older adults are at a similar risk for acquiring HIV. Additionally, screenings for HIV/STD tend to be lower among older adults, with this group seeing themselves at less risk for HIV/STD compared to their younger counterparts. Limited information exists concerning older bisexual men outside examining aggregated populations of sexual minority men (e.g., MSM). The purpose of this exploratory study was to examine the sexual health, behaviors, and evaluation of last sexual event among older (≥ 50 years old) compared to younger (< 50 years old) bisexual men. Data were collected in collaboration with a social and sexual networking website catering to men who have sex with men. Findings suggest that older bisexual men continue to be sexually active and that strategies need to be developed to better reach this population regarding HIV/STD prevention and education.